Early autologous cranioplasty: complications and identification of risk factors using virtual reality visualisation technique. (2nd November 2019) - Zawy Alsofy, Samer; Stroop, Ralf; Fusek, Ivo; Sakellaropoulou, Ioanna; Lewitz, Marc; Nakamura, Makoto; Ewelt, Christian; Fortmann, Thomas
Abstract: Background: Cranioplasty (CP) of autologous bone flap after decompressive craniectomy (DC) is known to be associated with a high complication rate, particularly bone flap resorption (BFR). In a retrospective study, we used a novel virtual reality (VR) visualisation technique to identify and evaluate risk factors associated with CP. Method: Twenty-five patients underwent early autologous CP. All complications were recorded. Cranial computed tomography scans were visualised via the VR software to access the fitting accuracy of the bone flap (bone flap size, gap width at trepanation cutting edge, extent of osteoclastic extension). Results: An overall complication rate of 44% was seen, and BFR was the most common (36%). Only 'osteoclastic extension of trepanation' ( p   =   .04) was a significant risk factor for BFR. The factors 'indication for DC' ( p   =   .09) and 'size of bone flap' ( p   =   .09) had a tendency towards influencing the rate of BFR, while 'age' ( p   =   .68), 'time interval between DC and CP' ( p   =   1.00), and 'gap width' ( p   =   .50) were not considered to influence the BFR rate. Conclusions: DC and subsequent CP is a complication-prone procedure. Therefore, it is relevant to identify and quantify probable risk factors for the most common complications, such as BFR. Here, we found that the extent of osteoclastic extension may impair the patient's healing process. Our investigation was made considerably easier by using the novel VR visualisation technique, which allows parallax free measurements of distances in 3D space.